MODIFIKASI PEREDAM SUARA (KNALPOT) MESIN DIESEL TRAKTOR RAMAH LINGKUNGAN - Djasbah, Sunandar; Lahming, Lahming; Jamaluddin P, Jamaluddin P (Universitas Negeri Makassar, 2018)
The purpose of this study to determine the magnitude of the effect of diesel engine modifications to the level of tractor noise and the magnitude of the effect of zeolit stone against the eco-friendly exhaust. This research is a design and engineering research by modification of environmentally friendly diesel engine exhaust. The data obtained in the analysis by compared the efficiency of the tool before the modification will then become a reference in making a description of the results of the modified muffler. Based on the results of the study that the modification of the eco-friendly diesel exhaust shows the exhaust noise level before modification of the maximum average of 94.77 dB and at least 90.23 dB and after modification average 94.59 dB and at least 89.51 dB. and the level of exhaust fumes diesel engine exhaust show average already modified 0,010633 gram and before modification show average 0,026868 gram